Antiepileptic Drugs, Polypharmacy, and Quality of Life in People Living with Epilepsy Managed in General Practice - Moran, Samuel; Peterson, Chris; Blackberry, Irene; Cook, Mark; Walker, Christine; Furler, John; Shears, Graeme; Piccenna, Loretta (International Journal of Epilepsy, 2020)
Objective Recently, instances of general practitioners (GPs) prescribing antiepileptic drugs (AEDs) have increased. We aimed to investigate the use of AEDs in a community sample of people with epilepsy and the effect on quality of life (QoL).Methods Responses from the Australian Epilepsy Longitudinal Study (AELS), Pharmaceutical Benefit Scheme (PBS), and Medicare Benefit Scheme (MBS) data were used. Linear regression was used to investigate the relationship between the numbers of AEDs and QoL.Results Fifty people with epilepsy were prescribed an average of two AEDs. The most common were lamotrigine, sodium valproate, and levetiracetam. Eighty-two percent were prescribed medications from two or more categories of medications. A lower QoL at wave 2 of the AELS was significantly associated with a higher number of AEDs.Conclusion Given the high number of people with epilepsy being cared for in general practice, GPs must understand the risks and benefits of epilepsy monotherapy, polytherapy, and polypharmacy.
Keywords: antiepileptic drugs; epilepsy; quality of life